The role of new firms: Births, deaths and job generation - Birley, Sue (Strategic Management Journal, 1986)
Abstract The contribution of both new and small firms towards economic recovery is now universally accepted as significant. What is still unclear, however, is the extent of that contribution, particularly with regard to the new firm. Despite this, governments at all levels, federal, state and county, have designed strategies for fostering entrepreneurial activity. With little specific knowledge of the target population, these strategies have been either general in nature or based on economic theory, and, as a consequence, little is known about whether they have been effective in affecting the natural process, and in what geographic locations. This research studied the whole population of new firms started in St. Joseph County, Indiana, between 1977 and 1982. It was concerned with both birth and death patterns, and the net jobs generated. The results confirmed the general findings of others that new firms play a significant role in job generation. Over the period, the number of jobs created by a new firm was a consistent 2.9 per cent of the total number of jobs in the industrial sectors studied. Moreover, this exceeded the 1.75 per cent of jobs lost through firms withdrawing from the labour market. Within this, activity in both firms and jobs was found to be centred in only a few SIC categories, and the results of this research suggest that simple tests of volatility and gain will help to focus strategic plans for aid on those sectors where the natural process is already generating the most new jobs.